Properties of Platinum Sub-Nanoclusters on Graphene Nano Sheets at Cathode - Siburian, Rikson; Bukit, Minsyahril (Institut Teknologi Bandung, 2014)
The catalytic activities of Pt subnano-clusters on graphene nanosheets (GNS) for oxygen reduction reaction (ORR) catalysts have been examined. The ORR activity of Pt on GNS (0.99 V) is higher than on carbon black (CB) commercial catalyst (0.94 V versus RHE). A core level shift of Pt 4f in XPS indicates that Pt is chemically interacted with GNS. It has been ascribed to difference in the interface interaction between Pt and graphene via different strength of the π–d hybridization. Keywords: Pt, Graphene nanosheet, Pt subnano-clusters, ORR. Sifat-sifat Pt Sub-Nanocluster pada Graphen Nano Sheets (GNS) di Katoda Abstrak Aktivitas katalis dari Pt subnano-kluster dengan menggunakan material pendukung graphen nano-sheet (GNS) untuk katalis reaksi reduksi oksigen (RRO) telah diuji. Aktivitas RRO dari Pt/GNS (0.99 V) lebih tinggi dari katalis komersial Pt CB (0.94 V versus RHE). Pergeseran tingkat pusat Pt 4 f pada data XPS mengindikasikan bahwa terjadi interaksi kimia antara Pt dan graphen melalui hibridisasi π–d. Kata kunci: Pt, Graphen nano-sheet, Pt subnano-kluster, RRO.